Multiple unilateral craniopathies (Guillain-Alajouanine-Garcin syndrome) resulting from a malignancy of the external auditory canal: a case report - Ang, Kevin Royce G.; Rivera, Ceferino L.; Almelor, Francis A. (International Journal of Research in Medical Sciences, 2024)
Garcin syndrome (or Gullain-Alajouanine-Garcin syndrome) was first described in the year 1926, as a paralytic unilateral cranial syndrome consisting of multiple cranial nerve palsies, without findings pointing towards increased intracranial pressure or long tract involvement. A 54-year-old female presented to us initially with ptosis and lateral rectus palsy of the right eye, later on, followed by progressive hearing loss on the right ear, right facial hemianesthesia, and progressive ipsilateral facial paralysis. A mass at the external auditory canal was seen during otoscopy, and a biopsy revealed squamous cell carcinoma. Contrast-enhanced neuroimaging also showed an enhancing mass lesion at the right skull base.